Barriers and facilitators to offering palliative care to patients with heart failure: a mixed-methods systematic review using the COM-B model and theoretical domains framework - Mengyun Peng; Yifu Lu; Wenping Mo (BMJ Open)
Objectives Despite palliative care (PC) potentially improving quality of life, only a tiny proportion of patients with heart failure (HF) are receiving PC. Globally, PC for HF patients faces several challenges; however, a systematic assessment of the barriers and facilitators to PC of patients suffering from HF is lacking. We aimed to identify barriers and facilitators to offering PC to HF patients.Design The mixed-methods systematic review was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis statement.Data sources PubMed, CINAHL, MEDLINE, PsycINFO, Web of Science were searched from onset of literature database to 24 March 2025.Eligibility criteria We included both qualitative studies and quantitative studies addressing barriers and facilitators to offering PC to patients with HF reported by healthcare providers, patients, family members and caregivers.Data extraction and synthesis Data extraction was done independently by two reviewers, and quality assessment was completed using the mixed-methods appraisal tool. The Capabilities-Opportunities-Motivations-Behaviour (COM-B) model and the Theoretical Domain Framework (TDF) were used to identify potential barriers and facilitators.Results 48 studies were included out of 4168. 289 items related to barriers and 88 items related to facilitators were categorised into 72 themes. These themes were found to align with at least one of the 14 TDF domains and the COM-B model. ‘Environmental context and resources’ (eg, lack of time, human, facilities and equipment resources; 77.2% of barriers vs 22.8% of facilitators), ‘knowledge’ (eg, insufficient awareness and knowledge of PC and/or needs; 91.8% of barriers vs 8.2% of facilitators) and “‘social influences’ (eg, limited communication and collaboration between healthcare professionals; 58.7% of barriers vs 41.3% of facilitators) were the three TDF domains that encoded the largest amount of data.Conclusions This review identified key barriers to PC for HF patients, primarily involving resource limitations, knowledge gaps and poor interdisciplinary collaboration. Findings highlight the need for targeted interventions addressing systemic and knowledge-related challenges.PROSPERO registration number CRD42023484807.